A Brain on a Roller Coaster: Can the Dopamine Reward System Act as a Protagonist to Subdue the Ups and Downs of Bipolar Disorder?. (October 2018) - Arjmand, Shokouh; Behzadi, Mina; Stephens, Gary J.; Ezzatabadipour, Sara; Seifaddini, Rostam; Arjmand, Shahrad; Shabani, Mohammad
One of the most interesting but tenebrous parts of the bipolar disorder (BD) story is the switch between (hypo)mania and depression, which can give bipolar patients a thrilling, but somewhat perilous, 'ride'. Numerous studies have pointed out that there are some recognizable differences (either state-dependent or state-independent) in several brain regions of people with BD, including components of the brain's reward system. Understanding the underpinning mechanisms of high and low mood statuses in BD has potential, not only for the development of highly specific and selective pharmaceutical agents, but also for better treatment approaches and psychological interventions to manage BD and, thus, give patients a safer ride. Herein, we review evidence that supports involvement of the reward system in the pathophysiology of mood swings, with the main focus on the mesocorticolimbic dopaminergic neural circuitry. Principally using findings from neuroimaging studies, we aim to signpost readers as to how mood alterations may affect different areas of the reward system and how antipsychotic drugs can influence the activity of these brain areas. Finally, we critically evaluate the hypothesis that the mesocorticolimbic dopamine reward system may act as a functional rheostat for different mood states.